Impact of the “Mengabu (Facing Ash Storms) Disaster Preparedness” Program on Adolescents’ Knowledge About Disaster Preparedness in Kresik Tuo Village, Kayu Aro District, Kerinci Regency, Jambi - Andi Subandi; Dwi Noerjoedianto; Elsa Volinda Sary (International Journal of Health and Social Behavior, 2024)
Natural disasters have become an integral part of people's lives in Indonesia, disrupting daily activities and causing significant impacts. Indonesia, located in the Ring of Fire, faces a high risk of volcanic eruptions, including the active Mount Kerinci which has the potential to cause disasters such as volcanic ashfall. Kresik Tuo Village, located near Mount Kerinci, faces a direct threat from this eruption. The community, especially the youth, need to improve their preparedness and knowledge to deal with potential disasters. The "MENGABU Siaga dalam Bencana" program is designed to improve the preparedness of the Kresik Tuo Village community in dealing with potential volcanic ashfall, with the hope of contributing to the development of community preparedness strategies in disaster-prone areas. To improve the knowledge of youth in Kresik Tuo Village related to disasters and disaster preparedness. The study used the Pre-Experimental research method with a Prepost Test Design. Sampling used a non-probability sampling technique with convenience sampling according to the inclusion and exclusion criteria of 40 respondents. Wilcoxon test shows that there is a significant increase in the knowledge of youth preparedness for the eruption of Mount Merapi after being given the "Mengabu Siaga dalam Bencana" program. All respondents experienced an increase in knowledge, as indicated by a positive ranks value of 40 and a p value = 0.000. Conclusion: The results of the study indicate that there is a significant effect of the "Mengabu (Mengabu Storm Ash) Siaga Dalam Bencana" Program on Youth Preparedness Knowledge for Disasters in Kresik Tuo Village, Kayu Aro District, Kerinci Regency, Jambi in increasing youth knowledge.